(untitled) (Revista BOEM, 2025)
Inclusion issues permeate the discussions on the teaching of mathematics, highlighting the needs and difficulties of both students and teachers who face situations for which they often lack knowledge and skills, but which require a welcoming and inclusive teaching practice . It is in this context that we present an experience built in the process of teaching mathematics to a blind student, student of a Pedagogy course. Such experience stems from the analysis of a teaching practice based on the use of tactile materials, developed in the discipline Mathematics in Early Childhood Education and Early Years of Elementary School, at the Center for Higher Studies in Parintins, in the state of Amazonas. The objective of the activity developed was to analyze the reach and limitations presented by tactile materials in the learning of a future blind teacher. The results obtained confirm that the inclusion of a student with a disability is not done only with his insertion in the classroom. A careful look from the teacher is necessary to choose teaching strategies and this requires the development of skills from their initial training.